User-Centric Design for Mathematical Web Services. (6th March 2014) - Sheeba, Adlin; Arumugam, Chandrasekar
Abstract : A web service is a programmatically available application logic exposed over the internet and it has attracted much attention in recent years with the rapid development of e-commerce. Very few web services exist in the field of mathematics. The aim of this paper is to seamlessly provide user-centric mathematical web services to the service requester. In particular, this paper focuses on mathematical web services for prepositional logic and set theory which comes under discrete mathematics. A sophisticated user interface with virtual keyboard is created for accessing web services. Experimental results show that the web services and the created user interface are efficient and practical.